COMBATANT STATUS UNDER INTERNATIONAL HUMANITARIAN LAW: LEGAL IMPLICATIONS FOR INDONESIAN NATIONAL ARMY OPERATIONS IN SEPARATIST CONFLICTS - Gumelar, Laksono M. A.; Amrullah, Rinaldy; Becánics, Adrienn; Putri, Ria Wierma (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2025)
The armed conflict between the Indonesian National Army and separatist groups in Papua shows the characteristics of a non-international armed conflict (NIAC) based on international humanitarian law (IHL). However, the legal status of Indonesian National Army soldiers in this conflict has not been clearly defined in the national legal system, thus creating ambiguity regarding their protection and accountability. This study aims to analyze the combatant status of Indonesian National Army soldiers in NIAC based on international legal instruments and national regulations. Through a normative legal approach comparisons with other countries such as Colombia, Philippines, and Hungary are examined to assess legal gaps and best practices. The research findings indicate that, although combatant status is not formally recognized in NIAC, the fundamental principles of IHL remain applicable to all parties. The study concludes that Indonesia must reform its legal framework to ensure both the protection of soldiers acting lawfully and accountability for IHL violations. The research contribution i the development of an understanding of international humanitarian law (IHL) and the formation of national policies related to the legal status of military members in non-international armed conflicts (NIAC).